Umbanda e sensibilidade ecológica: um estudo em duas casas em Goiânia - Machado, Sandra Maria Chaves (2020)
This research fits in the line of Cultures, Representations and Symbolic Practices of the Postgraduate Program in Sociology of the Federal University of Goiás. The study aims to investigate the Umbanda’s relations with nature, refining the encounter between its cosmovision, of a symbolic nature, and the ecological sensitivity that is so required in todays Society. In addition, through its offering processes, intends to verify the possibility of influence of the eco-spirituality vision, of some of its proselytes, in the adaptability of rituals. Two Umbanda houses were studied during a period of almost three years in the capital of Goiás. The research is referenced by scholars of the Sociology of Religion, such as Max Weber, Roger Bastide, Peter Berger, Reginaldo Prandi, Antônio Boaes, Rosalira Oliveira, Lísias Negrão, and also in the contribution of Social Sciences authors, like Mercedes Lopes, among other authors such as Elenita Malta Pereira, Leonardo Boff and Riley Dunlap. The metodology includes participatory observations of the common rituals and the application of questionnaires, with the NEP scale, which indicates the interviewee's 'ecological awareness'. The analyses indicate the existence of an ecological sensitivity between adherents, but one that did not come from religion itself, despite being reinforced by it. In addition, it was also noticeable some adaptations to the new, which is typical of Umbanda, but still as a trend, in the area of environmental preservation in its rites, such as waste disposal, among other actions.